2009
DOI: 10.1021/es8011595
|View full text |Cite
|
Sign up to set email alerts
|

PCNs, PCDD/Fs, and Non-orthoPCBs, in Water and Bottom Sediments from the Industrialized Norwegian Grenlandsfjords

Abstract: Chlorinated toxic planar aromatic compounds were analyzed in the heavily industrialized Grenlandsfjords, which is a system of silled fjords in southern Norway. Surface water samples contained 7.4-160 ng/m3 polychlorinated dibenzo-p-dioxins and furans (PCDD/Fs), 14-410 ng/m3 polychlorinated naphthalenes (PCNs), and 0.31-2.4 ng/m3 non-orthochlorinated biphenyls (non-orthoPCBs). The concentrations of PCDD/Fs were about 300 times higher than in the Baltic Sea. Highest level of the compounds wasfound near a magnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…The enrichment of lower chlorinated congeners in our study corresponded with many reports that reveal the enrichment of low molecular weight PCB congeners in marine sediments and waters from high latitudes (Gustafsson et al, 2001;Sericano et al, 2001;Strachan et al, 2001;Savinov et al, 2003;Ishaq et al, 2009). This enrichment seems to be explained by their more efficient atmospheric transport resulting from their relatively higher vapor pressure from sources in the industrialized northern temperate latitudes between 30-60°N, where around 86% of global P PCBs consumption occurs (Wania and Mackay, 1993; AMAP, 2004), and the higher fluxes of air-seawater exchange in the lower ambient temperature area (Iwata et al, 1993;Iwata et al, 1994a;Iwata et al, 1994b).…”
Section: Homologue Pattern Of Pcbs and Their Possible Sourcesupporting
confidence: 91%
“…The enrichment of lower chlorinated congeners in our study corresponded with many reports that reveal the enrichment of low molecular weight PCB congeners in marine sediments and waters from high latitudes (Gustafsson et al, 2001;Sericano et al, 2001;Strachan et al, 2001;Savinov et al, 2003;Ishaq et al, 2009). This enrichment seems to be explained by their more efficient atmospheric transport resulting from their relatively higher vapor pressure from sources in the industrialized northern temperate latitudes between 30-60°N, where around 86% of global P PCBs consumption occurs (Wania and Mackay, 1993; AMAP, 2004), and the higher fluxes of air-seawater exchange in the lower ambient temperature area (Iwata et al, 1993;Iwata et al, 1994a;Iwata et al, 1994b).…”
Section: Homologue Pattern Of Pcbs and Their Possible Sourcesupporting
confidence: 91%
“…The PCN congener profiles emitted from thermal processes and present in technical PCN mixtures have been compared in a number of studies (Jarnberg et al, 1999;Ishaq et al, 2003Ishaq et al, , 2009). Several congeners, including CNs 45/36, CN 54, CNs 66/67, and CN 73 have been widely recognized as being indicators of PCN emissions from thermal processes, because they are relatively abundant in emissions from thermal processes, but are present at much lower concentrations in Halowax mixtures (Meijer et al, 2001;.…”
Section: Homolog Distributions and Congener Profiles In Pcn Emissionsmentioning
confidence: 99%
“…PCN concentrations have also been measured in various environmental matrices in a number of regions (Jarnberg et al, 1997(Jarnberg et al, , 1999Krauss and Wilcke, 2003;Helm et al, 2004;Jaward et al, 2004;Herbert et al, 2005;Lee et al, 2007;Ishaq et al, 2009). Studies of PCNs in the environment have shown that PCNs can contribute a greater proportion than the PCDD/Fs and polychlorinated biphenyls (PCBs) to the dioxin-like toxicity (i.e., the toxic equivalence, TEQ) in soils, sediments, and biota in specific areas that are surrounded by industrial plants (Kannan et al, 1998(Kannan et al, , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with PCDD/Fs and dl-PCBs, investigations on PCNs, PeCBz and HxCBz emissions to the air from magnesium smelting processes are poorly reported. Such information is limited to unintentional POPs monitoring studies in environmental matrices, such as water, sediments and biota around magnesium plants (Tolley and Blais, 2007;Ishaq et al, 2009). Thus, the development of unintentional POPs inventories from magnesium smelting processes in China is crucial for evaluation of unintentional POPs releases from magnesium industries worldwide.…”
Section: Introductionmentioning
confidence: 99%